Effect of web-based training on public health nurses' program implementation capacity: a randomized controlled trial - Keiko Miyamoto; Reiko Okamoto; Keiko Koide; Mirei Shimodawa (BMC, 2024)
Abstract Background Health service development aims to close the gap between evidence and practice by adopting and appropriately utilizing the latest findings. To address this gap, dissemination and implementation research has been promoted and developed. Despite promoting evidence-based programs over the years, public health nurses have had few training opportunities in evidence-based public health. This study evaluated the effectiveness of a web-based training in building the basic program implementation capacity of public health nurses with two to five years of experience. Methods We developed a simulation-powered web-based training according to an Implementation Degree Assessment Sheet for health programs. This was a randomized, single-blind, parallel-group trial. The primary outcome, the result of implementation capacity for public health nurses, was assessed by the total score of the Implementation Degree Assessment Sheet, and scores for its five domains. The secondary outcome was evaluated by the level of understanding. The primary outcome was analyzed utilizing the t-test and analysis of covariance, whereas the secondary outcome was assessed utilizing the U-test and Quade's analysis of covariance. Data were collected directly before intervention (T1: baseline), immediately post-intervention (T2), and four weeks post-intervention (T3: endpoint). Results The 197 participants were randomly allocated to either the intervention group (n = 98) or the control group (n = 99). A full analysis set of 152 samples and a per-protocol set of 104 samples were analyzed. The intervention group exhibited a significantly higher total score and five domain-wise scores at the endpoint compared with the control group. The disparity between the endpoint and baseline scores was significantly larger for the intervention group for all scores. The level of understanding was significantly higher in the intervention group than in the control group at T2 and T3. The effect size of the total score was higher in the full analysis set (Cohen's d = 0.5) than in the per-protocol set (d = 0.48). Conclusions This web-based training was effective in building the program implementation capacity of participants four weeks post-intervention. Trial registration University Hospital Medical Information Network Center Clinical Trials Registry UMIN000048421.